Morpho-physiological growth performance and phytoremediation capabilities of selected xerophyte grass species toward Cr and Pb stress - Farooq, Taimoor Hassan; Rafay, Muhammad; Basit, Hamza; Shakoor, Awais; Shabbir, Rubab; Riaz, Muhammad Umair; Ali, Baber; Kumar, Uttam; Qureshi, Kamal Ahmad; Jaremko, Mariusz (Frontiers in Plant Science, 2022)
Being sessile organisms, plants cannot escape unwanted changes in the environment. The rapid human population explosion caused significant environmental problems. Heavy metals produced through various sources can cause severe damage to living organisms. The study was planned to evaluate four grass species' morpho-physiological growth characteristics and phytoremediation capabilities under chromium (Cr) and lead stress (Pb) in the arid climate. Typha angustifolia, Tragus roxburghii, Aeluropus logopoides and Cenchrus ciliaris grass species were used for the study. One-year-old stubbles from the Cholistan desert were used for the experiment. Cr treatments in the form of K2Cr2O7 were applied at 0, 20, 40, and 80 mg L-1, whereas Pb was applied as PbCl2 at 0, 50, 200 and 500 mg L-1 as control, low, moderate and high-stress, respectively. After six weeks of heavy metals treatments, plants were harvested and analyzed for growth performance and phytoremediation capabilities. Results depicted that, regarding morphological attributes, T. angustifolia performed better, followed by C. ciliaris; no clear pattern was observed for T. roxburghii and A. logopoides. The CO2 assimilation rate (Co2d) and water use efficiency (WUE) increased as the heavy metal stress increased in all species under both metals. In contrast, total chlorophyll content was higher under low stress. Other physiological parameters, such as relative humidity (RHd), net photosynthetic rate (A), transpiration rate (E), stomatal conductance (Gs), leaf internal CO2 concentration (Ci) and membrane stability index (MSI) gradually decreased as the Cr, and Pb stress levels increased among all the species. Moreover, Cr and Pb absorption contents of T. angustifolia were higher than the other three species at each stress level. Overall, T. angustifolia thrived against heavy metals stress and showed higher biomass, maximum photosynthetic measurements, WUE and higher metal absorption among all the selected species. Results concluded that although all the selected species behaved fine under stress conditions, T. angustifolia performance was better; thus, it can be used to remediate the soil near industrial estates.